2008
DOI: 10.1593/neo.08320
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled-7 as a Potential Therapeutic Target in Colorectal Cancer

Abstract: We investigated whether one of the Wnt receptors, frizzled-7 (FZD7), functions in the canonical Wnt signaling pathway of colorectal cancer (CRC) cells harboring an APC or CTNNB1 mutation and may be a potential therapeutic target for sporadic CRCs. The expression level of FZD gene family members in colon cancer cells and primary CRC tissues were determined by real-time PCR. Activation of the Wnt signaling pathway was evaluated by TOPflash assay. The expression level of Wnt target genes was determined by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
84
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 26 publications
10
84
0
1
Order By: Relevance
“…Transient transfection of FZD7_siRNA prepared for this study into colon cancer HCT-116 or HT-29 cells gave rise to a significant suppression of cell viability (Figure 2A), confirming our previous finding (Ueno et al, 2008). This also seems to be consistent with a previous finding that siRNA inhibition of FZD7 decreased the viability of mesenchymal stem cells (hMSCs; Song et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Transient transfection of FZD7_siRNA prepared for this study into colon cancer HCT-116 or HT-29 cells gave rise to a significant suppression of cell viability (Figure 2A), confirming our previous finding (Ueno et al, 2008). This also seems to be consistent with a previous finding that siRNA inhibition of FZD7 decreased the viability of mesenchymal stem cells (hMSCs; Song et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the down-regulation of FZD7 with Small-interfering RNA (siRNA) in colon cancer cells resulted in decreased in vitro invasion activity (Ueno et al, 2008), which is consistent with previous findings that inhibition of FZD7 expression with dominant-negative mutant construct or siRNA reduced the motility of hepatocellular carcinoma cells (Merle et al, 2004) or colon cancer cells (Vincan et al, 2007), respectively. These data suggest that FZD7 may be important in the invasion and metastasis of CRC.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Enhanced autocrine Wnt signaling (Bafico et al, 2004) and epigenetic silencing of genes encoding endogenous extracellular Wnt inhibitors (Suzuki et al, 2004) provide a positive selection advantage to cells carrying b-catenin pathway mutations (Barker and Clevers, 2006;Polakis, 2007;MacDonald et al, 2009). In this setting, frizzled receptor activation and enhanced Wnt expression drive positive cancer cell selection (Vider et al, 1996; Smith et al, An SFRP-like frizzled motif blocks tumor growth E Lavergne et al 1999; Dimitriadis et al, 2001;Holcombe et al, 2002;Ueno et al, 2008). Consequently, extracellular Wnt inhibitors such as SFRPs (Taketo, 2004), Wnt inhibitory factor-1 (Hu et al, 2009) or anti-Wnt1 antibodies (He et al, 2005) block tumor cell growth in cells carrying mutant b-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…In a majority of tumours, aberrant activation of the Wnt/b-catenin is the consequence of APC, Axin or b-catenin gene mutations (Lustig and Behrens, 2003). Moreover, it has been shown that overactivation of the Wnt signalling pathway is due to the overexpression of different FZD receptors in a variety of cancers (Milovanovic et al, 2004;Merle et al, 2005;Ueno et al, 2008). In NB, b-catenin has been shown to be strongly expressed and aberrantly localized in the nucleus in highly aggressive NB cells without MYCN amplification, whereas no b-catenin-specific mutations were identified (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%